(untitled) (FAN, TA’LIM, TEXNOLOGIYA VA ISHLAB CHIQARISH INTEGRATSIYASI ASOSIDA RIVOJLANISH ISTIQBOLLARI, 2025)
This article examines the use of jargon in professional communication, drawing insights from Business Writing for Dummies by Natalie Canavor. The piece discusses how jargon, while often valuable for precision and establishing credibility, can also obscure meaning and alienate audiences if used excessively or without consideration of context. Canavor’s approach is to prioritize clarity, ensuring that language is accessible to the intended audience without compromising professionalism. The article explores key principles from Canavor’s book, including the importance of understanding the audience, using jargon sparingly, explaining terms when necessary, and focusing on clear, effective communication. It also touches on the evolving role of jargon in the digital age, branding, and international communication. By highlighting practical strategies for balancing jargon in business writing, the article offers valuable insights for professionals seeking to communicate more effectively in a diverse, globalized workplace.